The Anti-Inflammatory Effects of Lipoxygenase and Cyclo-Oxygenase Inhibitors in Inflammation-Induced Human Fetal Glia Cells and the Aβ Degradation Capacity of Human Fetal Astrocytes in an Ex vivo Assay - Pihlaja R; Haaparanta-Solin M; Rinne JO (FRONTIERS MEDIA SA, 2022)
Chronic inflammation is a common phenomenon present in the background of multiple neurodegenerative diseases, including Alzheimer's disease (AD). The arachidonic acid pathway overproduces proinflammatory eicosanoids during these states and glial cells in the brain gradually lose their vital functions of protecting and supporting neurons. In this study, the role of different key enzymes of the eicosanoid pathway mediating inflammatory responses was examined in vitro and ex vivo using human fetal glial cells. Astrocytes and microglia were exposed to proinflammatory agents i.e., cytokines interleukin 1-beta (IL-1 beta) and tumor necrosis factor (TNF-alpha). ELISA assays were used to examine the effects of inhibitors of key enzymes in the eicosanoid pathway. Inhibitors for 5-lipoxygenase (5-LOX) and cyclo-oxygenase 2 (COX-2) in both cell types and 5-, 12-, and 15-LOX-inhibitor in astrocytes reduced significantly IL-6 secretion, compared to exposed glial cells without inhibitors. The cytokine antibody array showed that especially treatments with 5, -12, and -15 LOX inhibitor in astrocytes, 5-LOX inhibitor in microglia and COX-2 inhibitor in both glial cell types significantly reduced the expression of multiple proinflammatory cytokines. Furthermore, human fetal astrocytes and microglia were cultured on top of AD-affected and control human brain sections for 30h. According to the immunochemical evaluation of the level of total A beta, astrocytes were very efficient at degrading A beta from AD-affected brain sections ex vivo; simultaneously added enzyme inhibitors did not increase their A beta degradation capabilities. Microglia were not able to reduce the level of total A beta during the 30h incubation time.